Evaluating the knowledge of sports participants regarding dental emergency procedures - Mori, Graziela Garrido [UNESP]; Mendonça Janjacomo, Daniela Maria de [UNESP]; Castilho, Lithiene Ribeiro [UNESP]; Poi, Wilson Roberto [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
Dental trauma is a common consequence of sports practice to which emergency treatment is critical. The purpose of this study was to evaluate the knowledge of sports participants about dental trauma procedures, particularly tooth avulsion. A specific questionnaire concerning concepts, experiences and behaviors after dental trauma and the use of mouthguard was standardized and validated with 80 people. The validated questionnaire was then distributed to 310 sports participants. The results showed that 28.4% had experienced a kind of dental trauma; 42.6% would look for a dentist for treatment; 51.7% reimplanted or would reimplant the avulsed tooth; 6.5% would maintain the avulsed tooth in milk. Although 47.4% of the participants were aware of the possibility of accidents during sports practice, only 13.9% reported to use a mouthguard. This study showed an overall lack of knowledge of sportsmen and sportswomen with regards to tooth avulsion, thus reinforcing the need for educational campaigns to improve the immediate emergency treatment of tooth avulsion.